KOLABORASI STRATEGIS BERSAMA BANK INDONESIA: MENINGKATKAN KUALITAS KEUANGAN UMKM KOTA PADANG MELALUI PENDAMPINGAN AKUNTANSI DENGAN APLIKASI SIAPIK - Sanda Patrisia Komalasari; Muhammad Wafiq; Ghina Luqyana Ref; Rayna Kartika; Rita Rahayu (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2024)
This activity aims to train and assist several MSMEs in Padang City in utilizing the SIAPIK Application in their business. SIAPIK application is an application from Bank Indonesia for web-based accounting records designed to make it easier for MSMEs to carry out financial records. The methods used in this activity include socialization sessions, direct training and regular mentoring. Activities began with two days of socialization and training at the Bank Indonesia Building, West Sumatra, on 15-16 September 2023, followed by intensive assistance for three months until the end of December 2023. Socialization was conducted to introduce the SIAPIK Application and its benefits, while direct training provided MSMEs with an understanding of how to use the application—three months of assistance ensured that MSMEs could implement accounting records independently. The results of this activity show that all participants are proficient in using the SIAPIK Application. However, even though they have been provided with training and assistance, not all MSMEs carry out financial records regularly and comprehensively. This shows that there are internal obstacles among MSMEs that must be overcome. The conclusion from this activity is that intensive training and mentoring are very effective in improving the ability of MSMEs to use the SIAPIK Application. However, additional efforts are needed to achieve consistent financial records, such as providing incentives or ongoing support. The next recommended activity is to hold periodic follow-up sessions to monitor developments and motivate MSMEs to continue carrying out financial records in a disciplined manner using the SIAPIK Application.